Value of Tourist Attraction in Villa Kancil Kampoeng Soenda Bandung Regency - Didin Syarifuddin (International Journal of Nusantara Islam, 2020)
Villa Kancil Kampoeng Soenda is a natural and artificial tourist area, which is an attraction for tourists. But in 2019, the level of visits to Villa Kancil has decreased, possibly because of the development of tourist attractions that have not been maximized. This study aims to explain the causal relationship between tourist attraction and revisit intention and the value of Villa Kancil Kampoeng Soenda tourist attractions. The method used is descriptive and verificative to describe the research variables and explain the causal relationship between tourist attraction variables and revisit intention in Villa Kancil Kampoeng Soenda, through simple linear regression analysis. The population was tourists visiting during 2018, with a sample size of 200 people. The results of the study explained that Villa Kancil Kampoeng Soenda is an integrated tourist area that combines two natural and artificial tourist attractions, providing its own value for tourists who visit, namely the growth of satisfaction that leads to the growth of comfort and security during a visit at Villa Kancil Kampoeng Soenda. This tourist attraction was built by the authenticity of the rural environment landscape, a variety of natural and artificial attractions, the uniqueness of the natural environment in the form of rice fields and fish ponds, humidity and warmth typical of the tropics, a healthy and clean environment, and security guarantees during a visit. This tourist attraction provides a very high value for tourists, so it becomes a determining factor for the growth of repeat visits. The maximum supply of tourist attractions has an impact on the high value of tourist attractions, so that the impact on the high level of return visits to Villa Kancil Kampoeng Soenda.